How Qualitative Case Study Methodology Informs Occupational Therapy Practice: A Scoping Review. (January 2020) - Hercegovac, Suzana; Kernot, Jocelyn; Stanley, Mandy
Qualitative case study methodology (QCSM) is a useful research approach that has grown in popularity within the social sciences; however, it has received less attention in the occupational therapy literature. The current scoping review aims to explore how studies utilizing a QCSM help inform occupational therapy knowledge and practice. Electronic searches were conducted in April 2017, and the resultant 388 publications were screened by three reviewers in Covidence. In all, 27 publications met the inclusion criteria and were included in the scoping review. Case studies in the occupational therapy literature have explored phenomena relating to the delivery of intervention, theoretical concepts, clinical reasoning, and education and research methods and were situated in a range of different practice areas and contexts. QCSM is a valuable approach in occupational therapy research that contributes to the body of knowledge and theory that informs occupational therapy practice.